P–543 Inhibition of cell proliferation and extracellular matrix formation in human uterine leiomyomas by 5-aza–2'-deoxycitidine via Wnt/ β-catenin pathway. (6th August 2021) - Carbajo-García, M C; Corachán, A; Segura, M; Monleón, J; Escrig, J; Faus, A; Pellicer, A; Cervelló, I; Ferrero, H
Abstract: Study question: Is DNA methylation reversion through DNA methyltransferases (DNMT) inhibitors, such as 5-aza–2'-deoxycitidine, a potential therapeutic option for treatment of patients with uterine leiomyomas (UL)? Summary answer: 5-aza–2'-deoxycitidine reduces proliferation and extracellular matrix (ECM) formation by inhibition of Wnt/ β-catenin pathway on UL cells, suggesting DNMT inhibitors as an option to treat UL. What is known already: UL is a multifactorial disease with an unclear pathogenesis and inaccurate treatment. Aberrant DNA methylation have been found in UL compared to myometrium (MM) tissue, showing hypermethylation of tumor suppressor genes, which contributes to the development of this tumor. The use of DNMT inhibitors, such as 5-aza–2'-deoxycytidine (5-aza-CdR), has been suggested to treat tumors in which altered methylation pattern is related to tumor progression, as occurs in UL. Based on this, we aimed to evaluate whether DNA methylation reversion through 5-aza-CdR reduces cell proliferation and ECM formation in UL cells, being a potential option for UL medical treatment. Study design, size, duration: Prospective study comparing UL versus MM tissue and human uterine leiomyoma primary (HULP) cells treated with/without 5-aza-CdR at 0 µM (control), 2 µM, 5 µM and 10 µM for 72 hours. UL and MM tissue were collected from women without any hormonal treatment for the last 3 months (n = 16) undergoing myomectomy or hysterectomy due to symptomatic leiomyoma pathology. Participants were recruited between January 2019 and February 2020 at Hospital Universitario y Politecnico La Fe (Spain). Participants/materials, setting, methods: Samples were collected from Caucasian premenopausal women aged 31–48 years, with a body mass index of < 30 and without hormonal treatment. DNMT1 gene expression was analysed in UL vs MM tissue by qRT-PCR and activity of DNMT was measured in UL and MM tissue and cells by ELISA. 5-aza-CdR effect on proliferation was assessed by CellTiter test and Western blot (WB), apoptosis and ECM analyzed by WB and Wnt/ β-catenin pathway by qRT-PCR and WB. Main results and the role of chance: DNMT1 gene expression was increased in UL compared to MM tissue (fold change [FC]=2.49, p-value [p]=0.0295). Similarly, DNMT activity was increased in both UL compared to MM tissue and HULP cells versus MM cells (6.50 vs 3.76 OD/h/mg, p = 0.026; 211.30 vs 63.67 OD/h/mg, p = 0.284, respectively). After 5-aza-CdR treatment, cell viability of HULP cells was reduced in a dose dependent manner, being statistically significant at 10 µM (85.25%, p = 0.0001). Accordantly, PCNA protein expression was significantly decreased at 10 µM in HULP cells (FC = 0.695, p = 0.034), demonstrating cell proliferation inhibition. Additionally, 5-aza-CdR inhibited ECM protein expression in HULP cells in a dose-dependent manner being statistically significant at 10 µM for COLLAGEN I (FC = 0.654, p = 0.023) and PAI–1 (FC = 0.654, p = 0.023), and at 2 µM and 10 µM for FIBRONECTIN (FC = 0.812, p = 0.020; FC = 0.733, p = 0.035; respectively). Final targets of Wnt/ β-catenin pathway were decreased after 5-aza-CdR treatment, protein expression of WISP1 was significantly inhibited at 10 µM (FC = 0.699, p = 0.026), while expression levels of Wnt/ β-catenin target genes C-MYC (FC = 0.745, p = 0.028 at 2 µM; FC = 0.728, p = 0.019 at 10 µM) and MMP7 (FC = 0.520, p = 0.003 at 5 µM, FC = 0.577, p = 0.007 at 10 µM) were also significantly downregulated in HULP-treated cells vs untreated cells. Limitations, reasons for caution: This study has strict inclusion criteria to diminish epigenetic variability, thereby we should be cautious extrapolating our results to general population. Besides, this is a proof of concept with the inherent cell culture limitations. Further studies are necessary to determine 5-aza-CdR dose and adverse effects on UL in vivo. Wider implications of the findings: 5-aza-CdR treatment reduces cell proliferation and ECM formation through Wnt/ β-catenin pathway inhibition, suggesting that inhibition of DNA methylation could be a promising new therapeutic approach to treat UL. Trial registration number: Not applicable